Ecomorphology and foraging behaviour of Pacific boobies - Van Oordt, Francis (2018)
Wing size and shape, expressed as wing loading and aspect ratio respectively, together with bill morphology are parameters that can reveal differences related to the foraging ecology of seabirds. Six species of booby (Sulidae) that inhabit the Pacific are the focus of this study: four mainly pelagic species, Masked Booby Sula dactylatra, Nazca Booby Sula granti, Red-footed Booby Sula sula and Brown Booby Sula leucogaster, and two coastal species, Blue-footed Booby Sula nebouxii and Peruvian Booby Sula variegata. Pelagic boobies showed segregation among species in body mass and relative bill size, and they differed in wing morphology (wing loading and aspect ratio) from the coastal boobies. The coastal Peruvian and Blue-footed Boobies are largely allopatric but overlap in northern Peru. In their area of sympatry, they showed evidence of character displacement in body size and in wing and bill morphology, which suggests that competition plays an important role in sympatry. This study improves our understanding of ecological interactions among Pacific boobies and of how selective pressures have shaped their ecomorphology and foraging behaviours.